RISIKO POLA KONSUMSI DAN STATUS GIZI PADA KEJADIAN HIPERTENSI MASYARAKAT MIGRAN DI INDONESIA Risks of Consumption Patterns and Nutritional Status in the Incidence of Hypertension in Migrant Communities Indonesia - Annisa Destiani; Muhammad Atoillah Isfandiari; Risna Nur Fajariyah (Universitas Airlangga, 2021)
Hypertension cases in Indonesia have been increasing. Hypertension can be caused by controllable factors such as consumption patterns and nutritional status. This study was aimed to analyze the risk of fast food and instant noodle consumption patterns, as well as the risk of nutritional status on the incidence of hypertension in Indonesian migrant communities. This study used a cross-sectional design with 6,928 respondents. This study involved secondary data from the 5th batch of the Indonesian Family Life Survey (IFLS). The results showed that the majority of respondents were female (51.24%), adult age category (58.63%), frequent fast food consumption patterns (89.42%), frequent instant noodle consumption patterns (56.63%), and normal nutritional status (72.42%). The subjects with frequent consumption of fast food (OR = 1.49; CI = 1.041–2.130) and instant noodle (OR = 1.25; CI = 1.030–1.520) as well as overweight (OR = 3.90; CI = 3.154–4,838) and obesity (OR = 6.75; CI = 5,110–8,935) have higher risk to experience hypertension. Based on these results, it is recommended to migrants to maintain their consumption patterns by limiting their fast food and instant noodles intake and also to maintain the nutritional status to prevent hypertension